Acute overdose of antipsychotics and antidepressants by patient with paranoid schizophrenia - a case report - Anna Katarzyna Orzeł; Dominika Janeczko; Barbara Zofia Klatka; Magdalena Hołowczuk; Małgorzata Neścior-Piech; Michał Tchórz (Kazimierz Wielki University, 2019)
Introduction Despite developing strategies for treatment of people with schizophrenia, earlier mortality rate is still observed in this group of patients. One of the major causes remains suicides due to drug overdose. Main approach to the treatment of schizophrenia is pharmacotherapy that is based on antipsychotics. Yet, in order to sustain patients well being, medicaments from other groups may be introduced. Pharmacological treatment should be accompanied by psychotherapy to prevent suicidal attempts. Case report A 28 years old woman diagnosed with paranoid schizophrenia was brought by the ambulance and admitted to the Clinical Toxicology Department due to deliberate drug overdose. Her history indicated previous suicidal attempt. A patient took all her psychiatric medications that included 240 tablets of quetiapine (Ketrel a 200 mg), 100 tablets of zuclopenthixol (Clopixol a 25 mg), 100 tables of chlorprotixen, several tablets of escitalopram (Aciprex) and 12 tablets of bisoprolol (Bibloc a 5 mg) - in summary around 470 tablets. This suicidal attempt was probably the cause of abrupt drugs withdrawal after discharge from recent hospitalization in psychiatric department. Complications involved allo- and autodisorientation, enhancement of imperative auditory hallucinations and psychotic symptoms, respiratory failure and aspiration pneumonia. After admission, intensive symptomatic treatment was introduced in order to sustain living functions of the patients. Due to respiratory failure, she was in need of external mechanical ventilation. The end of hospitalization was followed by implementation of new drug (perazine) and transportation to Neuropsychiatric hospital for further diagnosis and treatment. Conclusion Process of pharmacotherapy in case of patients with schizophrenia should be continuously and precisely monitored by psychiatrists. Such control would minimize the chance of suicidal attempt. What is more, patient should not limit the therapy to drugs and psychiatric appointments, but also should attend to community health services.